2010
DOI: 10.2214/ajr.09.3410
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Pulmonary Embolism on CT Pulmonary Angiography

Abstract: Most patients (81%) showed complete resolution of PE on CT angiography after 28 days. PEs resolved faster in the main and lobar pulmonary arteries than in the segmental branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…However, studies using CT have shown differing results. In a previous study, emboli resolved at a faster rate in the main and lobar pulmonary arteries than in the segmental branches [19]. In another study, clots resolved faster in the peripheral arteries than in the central pulmonary arteries [17].…”
Section: Discussionmentioning
confidence: 82%
“…However, studies using CT have shown differing results. In a previous study, emboli resolved at a faster rate in the main and lobar pulmonary arteries than in the segmental branches [19]. In another study, clots resolved faster in the peripheral arteries than in the central pulmonary arteries [17].…”
Section: Discussionmentioning
confidence: 82%
“…Another possible explanation for a normal D-dimer result in patients with delayed presentation may be the complete or almost complete resolution of the pulmonary embolus. Stein et al 13 and Aghayev et al 14 performed retrospective reviews of patients diagnosed with PE and had a follow-up CTPA. Stein et al 13 found that there was complete PE resolution within 2–7 days of initial imaging in 40% of patients and Aghayev et al 14 report complete PE resolution within 14 days in 57% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stein et al 13 and Aghayev et al 14 performed retrospective reviews of patients diagnosed with PE and had a follow-up CTPA. Stein et al 13 found that there was complete PE resolution within 2–7 days of initial imaging in 40% of patients and Aghayev et al 14 report complete PE resolution within 14 days in 57% of patients. In all the time intervals studied, both studies found that decrease in clot burden and resolution was higher in the peripheral arterial emboli compared with central pulmonary artery emboli.…”
Section: Discussionmentioning
confidence: 99%
“…IPCs in the main and lobar pulmonary arteries are reported to resolve more quickly than those in the segmental branches [23], whereas other results have shown that peripheral clots resolve faster than clots in the main and lobar arteries [24]; however, these differences may be due to the limited spatial resolution or wide reconstruction slice-thickness of CTPA. The presence of residual IPCs did not have an effect on right heart strain in this study.…”
Section: Figmentioning
confidence: 91%